Role of facies cycles on the mid-upper Cretaceous Bangestan Reservoir rock typing in the Zagros Basin. (February 2023) - Khoshnoodkia, Mehdi; Mirzaei-Paiaman, Abouzar; Rahmani, Omeid; Adabi, Mohammad Hossein
Abstract: The principal objectives of this research were to examine the role of sedimentary cycles and tectonics in the Ahwaz Bangestan Reservoir quality, view the vertical and lateral changes of these sedimentary cycles, and identify rock typing units. There is an urgent need to understand how interpretive data are perceived among diagenetic events, sedimentary cycles, exposure surfaces, disconformities, carbonate fabric units, porosity-permeability relationship, wettability index, and relative permeability and capillary pressure vs. saturation curves. The Ahwaz Bangestan Sequence consists of Ilam and Sarvak Formations from the late Albian to Santonian Stages, in which disconformity surfaces separated the third-order sequences. Early diagenetic processes of the Bangestan sequence include meteoric dissolution and the deposit of marine cement. The meteoric diagenesis plays an essential role in the reservoir quality of these sequences and sedimentary cycles, and the burial cement process reduces the Bangestan Reservoir quality. The Bangestan sediments experience significant disconformity surfaces in the upper Cenomanian and Post-Turonian Stages. Meteoric waters affect these exposure surfaces to 50 m, increase porosity by about 15%, and have a permeability of 5 mD. With this, the results showed that there is a positive relationship between permeability and porosity data of the Bangestan sedimentary facies. In this regard, grainstone and packstone facies in the Ilam Formation demonstrated a higher reservoir quality than other facies, except for secondary chalky facies in Zone C1, where severe meteoric diagenesis occurred before lithification. Besides, the sedimentary model of the Bangestan Reservoir revealed six facies association, including tidal flat, lagoon, back shoal, rudist biostorm, shoal, and deep-marine with terrigenous layers. Given rock typing classification, four geological static rock typing (GSRT) were recognized with good correlation among lagoon, back shoal, rudist biostorm, and shoal facies association. The results demonstrated a positive relationship between permeability and porosity characteristics, leading to higher porosity and permeability in facies association of shoal and rudist biostorm with better GSRT. Besides, facies association of back shoal and lagoon with lower porosity and permeability represented worse GSRT. However, due to different diagenesis events, open-marine facies did not follow an adequate GSRT. Furthermore, three oil-wet geological dynamic rock typing (GDRT) and two water-wet GDRTs were identified, indicating the dynamic behavior of facies association. As a result, facies association with better reservoir quality (i.e., higher permeability and porosity) present higher GDRT, while facies association with worse reservoir quality (i.e., lower permeability and porosity) show lower GDRT. Graphical abstract: Image 1 Highlights: Meteoric diagenesis plays an important role in the reservoir quality of facies. Bangestan Reservoir involves two main disconformities of Cenomanian-Turonian. Grainstone and packstone facies represent better reservoir quality. Higher porosity and permeability, higher geological dynamic rock typing.